Evaluasi Media Mind Mapping dan Poster dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Mata Pelajaran PAI di SMA Al Islam Krian: Penelitian - Dimas Prasetyo; Maulidia Ilham Fadilah; Muhammad Farih Al Faaza; Ahmad Muhammad Ramadhan; Nadifa Salsabilah; Muhammad Bukhori; Masfufah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to evaluate the effectiveness of the use of Mind Mapping and Poster learning media in improving students' critical thinking skills in Islamic Religious Education subjects. The specifications of poster and mapping media are used to help students organize information and clarify relationships between concepts, which support the development of critical thinking skills. The study was conducted using a quantitative approach, involving Al Islam Krian High School students as subjects who were given learning materials using both media. Data collection techniques through observation, interviews, and documentation. Member Check is used in data analysis in this study as a reinforcement. The results of the study showed that Mind Mapping media helps students organize ideas and connect concepts that have been learned, while attractive Poster media provides visualizations that are easy for Al Islam Krian High School students to understand. Overall, the use of Mind Mapping and Poster media can increase student motivation and involvement so as to support the development of critical thinking skills of Al Islam Krian High School students in Sidoarjo.